Acidotoxicity in brain ischaemia. (25th October 2006) - Simon, R.; Xiong, Z.
Abstract : Intracellular calcium toxicity remains the central feature in the pathophysiology of ischaemic cell death in brain. Glutamate-gated channels have been thought to be the major sites of ischaemia-induced toxic calcium entry, but the failure of glutamate antagonists in clinical trials has suggested that glutamate-independent mechanisms of calcium entry during ischaemia must exist and may prove central to ischaemic injury. We have shown that ASICs (acid-sensing ion channels) in brain are glutamate-independent vehicles of calcium flux and transport calcium in greater measure in the setting of the two major neurochemical components of ischaemia: acidosis and substrate depletion. Pharmacological blockade of ASICs markedly attenuates stroke injury with a robust therapeutic time window of 5 h following stroke onset. Here, we describe this new mechanism of calcium toxicity in brain ischaemia and offer a potential new therapy for stroke.